2010
DOI: 10.1371/journal.pone.0015039
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular and Co-Evolutionary Context for Grazer Induced Toxin Production in Alexandrium tamarense

Abstract: Marine dinoflagellates of the genus Alexandrium are the proximal source of neurotoxins associated with Paralytic Shellfish Poisoning. The production of these toxins, the toxin biosynthesis and, thus, the cellular toxicity can be influenced by abiotic and biotic factors. There is, however, a lack of substantial evidence concerning the toxins' ecological function such as grazing defense. Waterborne cues from copepods have been previously found to induce a species-specific increase in toxin content in Alexandrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 63 publications
11
59
0
Order By: Relevance
“…Although this study found that grazers induced toxin production in dinoflagellates and this is supported by several studies on grazing effect to the toxin production in dinoflagellates, two upregulated genes that could be annotated in this study are unlikely to be directly involved in PSP toxin synthesis [48,[58][59][60].…”
Section: Environmental Stresssupporting
confidence: 70%
“…Although this study found that grazers induced toxin production in dinoflagellates and this is supported by several studies on grazing effect to the toxin production in dinoflagellates, two upregulated genes that could be annotated in this study are unlikely to be directly involved in PSP toxin synthesis [48,[58][59][60].…”
Section: Environmental Stresssupporting
confidence: 70%
“…If cooperative traits governing intraspecific interactions are common in mixed Alexandrium populations, the high phenotypic and genotypic diversity of these populations may be explained for example, by compatibility among these beneficial phenotypic traits in different strains. Such alternative traits may include for instance, chain formation, swimming speed, nutrient uptake capabilities, intrinsic growth rate and PST content [22,23,[69][70][71]. Indeed, the non-lytic strain Alex5 in our experiment contained the highest amount of PSTs (data not shown), a trait that potentially allows protection against grazing by copepods [22,23,69].…”
Section: Discussionmentioning
confidence: 79%
“…2B). A. minutum cells show species specific responses to copepod cues, where some copepods induce a several-fold increase in toxicity and others trigger weaker responses (10,12). The most potent inducer, Centropages typicus, was confirmed to have the highest proportion of the more potent copepodamides A-C, whereas weaker inducers had approximately three times lower proportion of copepodamides A-C.…”
Section: Discussionmentioning
confidence: 89%